Solvent-Free Enzymatic Synthesis of Dietary Triacylglycerols from Cottonseed Oil in a Fluidized Bed Reactor - Remonatto, Daniela [UNESP]; Santaella, Núbia [UNESP]; Lerin, Lindomar Alberto; Bassan, Juliana Cristina [UNESP]; Cerri, Marcel Otávio [UNESP]; de Paula, Ariela Veloso [UNESP] (MDPI, 2023)
The synthesis of structured lipids with nutraceutical applications, such as medium-long-medium (MLM) triacylglycerols, via modification of oils and fats represents a challenge for the food industry. This study aimed to synthesize MLM-type dietary triacylglycerols by enzymatic acidolysis of cottonseed oil and capric acid (C10) catalyzed by Lipozyme RM IM (lipase from Rhizomucor miehei) in a fluidized bed reactor (FBR). After chemical characterization of the feedstock and hydrodynamic characterization of the reactor, a 22 central composite rotatable design was used to optimize capric acid incorporation. The independent variables were cycle number (20–70) and cottonseed oil/capric acid molar ratio (1:2–1:4). The temperature was set at 45 °C. The best conditions, namely a 1:4 oil/acid molar ratio and 80 cycles (17.34 h), provided a degree of incorporation of about 40 mol%, as shown by compositional analysis of the modified oil. Lipozyme RM IM showed good operational stability (kd = 2.72 × 10−4 h−1, t1/2 = 2545.78 h), confirming the good reuse capacity of the enzyme in the acidolysis of cottonseed oil with capric acid. It is concluded that an FBR configuration is a promising alternative for the enzymatic synthesis of MLM triacylglycerols.
Keywords: acidolysis; enzyme; lipase; structured lipids; triacylglycerols